Förenliga motsatser? : En jämförande studie om aggregering och deliberation i två e-petitionssystem - Kristensson, Robin (Örebro universitet, Institutionen för humaniora, utbildnings- och samhällsvetenskap, 2013)
This essay sets out to compare political participation in two e-petition systems: The Malmö initiative in Malmö, Sweden, and Better Reykjavik in Reykjavik, Iceland. The main question of the essay concerns the aggregative and deliberative qualities of the Malmö initiative and Better Reykjavik, as well as the relationship between aggregation and deliberation. This main question is divided into four subqueries that lead the empirical analysis. These are: (1) Which similarities and differences in terms of design are there between the Malmö initiative and Better Reykjavik? (2) To what extent have these systems mobilized an aggregative political participation? (3) What similarities and differences are there concerning aspects of deliberation? and (4) What is the correlation between aggregation and deliberation like in the two e-petition systems? The method in use is a comparative cross-sectional study with a 'most similar research design'. The empirical material of the essay includes every petition published since the start of the systems in 2008, which makes it a total survey. The petitions are analyzed by way of quantitative content analysis. In addition, the essay includes a qualitative content analysis of the design of the e-petition systems. The empirical study shows that Better Reykjavik has engaged much greater political participation in both aggregative and deliberative matters than the Malmö initiative has. Most of the differences found concerning aggregation and deliberation can be explained with differences in the design of the e-petition systems. First, Better Reykjavik offers more opportunities for aggregative participation and deliberation than Malmö. Second, the likelihood of actually getting the petition read by local politicians is far greater in Reykjavik than in Malmö. Concerning the relationship between aggregation and deliberation, this study finds no signs of contradiction between the two. As this is not a zero-sum game, e-petition systems are considered to hold good potential for meeting Robert ...